Phylogenetic relationships and the effects of edaphic heterogeneity on the distribution of Wiborgia (Fabaceae) in the Greater Cape Floristic region - Moiloa, Ntwai (Department of Biological Sciences, 2016)
The Greater Cape Floristic Region (GCFR) is divided into two subregions, the Core Cape Subregion (CCR) and Extra Cape Subregion (ECR), which are mainly characterized by Fynbos and Succulent Karoo biomes, and are recognized among global biodiversity hotspots. The soils in the ECR are mostly shale derived and richer in nutrients compared to the CCR which is characterized by nutrient-poor sandstone soils mainly from the Cape System. The Fabaceae (Leguminosae) is the second largest family in the CCR with a total of about 764 species (belonging to 43 genera, of which 83% of the species are endemic to the CCR), and sixth largest in the ECR with about 140 species currently recognised with 39.3% of these species endemic to the ECR. Wiborgia Thunb. is a legume genus made up of 9 perennial shrub species of height 0.5-3.0 metres, with distinct ascending to erect habit, which share morphological similarities with some Lebeckia, especially sect. Viborgoides currently referred to as Wiborgiella. The aim of this dissertation was to understand the evolution and biogeography of the genus Wiborgia in the GCFR. This involved (i) inferring phylogenetic relationships within the genus using multiple molecular markers and testing the monophyly and the support of Dahlgren's (1975) morphological subgeneric classification; (ii) determining nutritional characteristics of soils occupied by different Wiborgia species and compare them with sites where Wiborgia species have not been recorded to occur and testing whether Wiborgia species occupy habitats with similar nutrient concentrations; (iii) evaluating the potential of Wiborgia species to grow and nodulate in soils from within and outside distribution range and characterizing of rhizobia nodulating Wiborgia species in field and glasshouse conditions. Phylogenetic relationships in Wiborgia were inferred using multiple molecular markers (ITS, rpl32-trnL, rps16, trnS-trnG, and trnT-trnL) and the data were analysed using model based approaches (Maximum Likelihood, Bayesian inference). Wiborgia was well supported as monophyletic and sister to both Wiborgiella and Aspalathus, with Wiborgiella humilis well supported as being part of the Wiborgiella clade. Within the Wiborgia clade, two strongly supported subclades were observed. In subclade 1, W. tetraptera was strongly supported as sister to W. fusca, whilst W. monoptera was strongly supported as sister to W. incurvata. In subclade 2, a novel well-supported sister relationship between W. mucronata and W. tenuifolia was observed. Wiborgia obcordata, the only species in Dahlgren's subgenus Wiborgia, was found to be embedded within subgenus Pterocarpia and thus the subgenera classification of Dahlgren was not supported. It was also identified that sister species pairs (W. incurvata and W. monoptera; W. fusca and W. tetraptera; W. tenuifolia and W. mucronata) all showed the tendency to co-occur or have overlapping distribution ranges, and showed subtle differences in floral morphology and habitats.